Towards emissions certification systems for international trade in hydrogen: The policy challenge of defining boundaries for emissions accounting. (15th January 2021) - White, Lee V.; Fazeli, Reza; Cheng, Wenting; Aisbett, Emma; Beck, Fiona J.; Baldwin, Kenneth G.H.; Howarth, Penelope; O'Neill, Lily
Abstract: Hydrogen as a fuel is clean burning, but production can cause substantial greenhouse emissions. Some buyers will prefer to pay a higher price to ensure purchase of low-embedded emissions hydrogen, but it is impossible to determine embedded emissions by examining the end product. Certification of embedded emissions will thus play a key role in the future of hydrogen as a low-emission energy carrier. The boundaries of the supply-chain elements covered in the emissions accounting of certification schemes will have substantial implications for emission-reduction incentives and international tradability. We review the boundary definitions of existing and emerging hydrogen certification schemes. Further, we provide an evidence-based assessment of the magnitude of emissions likely to occur within each boundary of the supply chain. We find varying approaches to boundary definitions in the surveyed schemes. The exclusion of feedstock or transport elements risks ignoring major fractions of supply-chain emissions. In order to balance tradability and emissions-reduction incentives, we recommend that hydrogen certification schemes be designed to follow a modular approach. This type of modular approach would place those with decision-making power over the relevant piece of the supply chain in the position of certifying the emissions within that supply-chain boundary. Highlights: In certifying low-carbon hydrogen it is important to consider the full supply chain. It is important to not neglect carbon in infrastructure and feedstocks. The boundaries of emissions accounting has substantial emissions implications. Current hydrogen strategies consider supply chain emissions inconsistently. Modular certification at well-defined boundaries could support trade.